Reduced COVID-19 morbidity and mortality in hemodialysis patients across the various Omicron sublineages—A retrospective analysis - Schuller, Max; Ginthör, Noemi Elisabeth; Paller, Astrid; Waller, Maximilian; Köstenbauer, Martin; Schreiber, Nikolaus Gustav Oskar; Schabhüttl, Corinna; Mischinger, Kathrin; Hafner-Giessauf, Hildegard; Rosenkranz, Alexander R.; Eller, Philipp; Eller, Kathrin (Frontiers in Public Health, 2023)
Hemodialysis patients are at particular risk of severe COVID-19 due to underlying health conditions and a weakened immune system. We analyzed SARS-CoV-2 infections in hemodialysis patients in southern Styria, Austria, to study the impact in this population. We observed 274 cases in five distinct waves between May 2020 and August 2022. In the initial four waves mortality was at around 20%, and roughly 60% needed to be hospitalized. Despite 167 infections during the fifth wave, in which the Omicron variant was dominant, mortality was almost non-existent and only 17% were hospitalized. Our findings are in line with previous reports, which have shown a marked reduction in morbidity and mortality with Omicron compared to previous variants. Previous vaccination was a protective factor in our hemodialysis population. Contributing to the existing literature, we found no difference between Omicron sublineages BA.4/5 and BA.1 and BA.2 infections with regards to disease severity and outcome in our hemodialysis population. Despite being considered a high-risk group, Omicron infections, regardless of sublineage, were mild in our broadly vaccinated hemodialysis population. Nonetheless, Omicron's high transmissibility resulted in a significant number of infections, which may present containment and financial challenges to dialysis units and health care systems.